Composite crystal form manganese-based catalyst, preparation method and application

By recycling and utilizing waste lithium batteries to prepare composite manganese-based catalysts with 3D structure and α and δ crystal forms, the problem of insufficient recycling and utilization of manganese-based transition metals and catalytic oxidation of toluene in waste lithium batteries is solved, and high efficiency is achieved Catalytic performance and stability.

CN119114055APending Publication Date: 2024-12-13JIANGSU UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311588442.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-11-24
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The prior art is difficult to effectively recover and utilize manganese-based transition metals in waste lithium batteries, and the catalyst's activity and stability during catalytic oxidation of toluene are insufficient, which affects the treatment effect of volatile organic matter.

Method used

By recycling the positive electrode of the used lithium manganate battery, a composite manganese-based catalyst with a 3D structure and having both α and δ crystal forms were prepared. The steps of leaching, mixing and drying of acid and reducing agent are used to form high-quality A catalyst with specific surface area and abundant oxygen vacancy.

Benefits of technology

The catalyst exhibits excellent activity during catalytic oxidation of toluene, with significantly improved conversion and COx yields, and a decrease in temperature of T90 and T50, indicating higher catalytic properties and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119114055A_ABST
    Figure CN119114055A_ABST
Patent Text Reader

Abstract

The invention discloses a composite crystal form manganese-based catalyst, a preparation method and application, the preparation method comprises the following steps: preparing waste lithium manganate battery positive active powder, and leaching the positive active powder by using acid and a reducing agent; mixing the leachate with alkali metal hydroxide, adjusting the pH value to 3-6, and adding potassium permanganate and deionized water to obtain a mixed solution; dissolving potassium permanganate and manganese salt in water to prepare a suspension; mixing the mixed solution with the suspension, and drying; and after the reaction is finished, filtering, washing, drying and calcining in sequence to obtain the composite crystal form manganese-based catalyst. According to the invention, the anode of the waste lithium manganate battery is recycled to prepare the composite manganese-based catalyst which contains a 3D structure and simultaneously has two crystal forms of alpha and delta, and T90 and T50 of the catalyst are greatly reduced when the catalyst is used for catalytically oxidizing toluene.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a composite crystal manganese-based catalyst, a preparation method and application thereof, and belongs to the technical field of catalyst preparation. Background Art

[0002] In recent years, with the rapid development of lithium-ion batteries (LIBs), their application scope has been greatly expanded, including portable electronic devices and new energy vehicles. Subsequently, a large amount of discarded LIBs will cause serious environmental pollution, public health problems, and natural resource depletion. In addition, waste LIBs are considered to be a waste stream with strategic value because they contain many important metals such as Li, Co, and Ni. Therefore, the effective recycling of waste LIBs has become a research hotspot. Compared with pyrometallurgical technology, hydrometallurgical processes have the advantages of high recovery rates of various metals, high product purity, low energy consumption, and less toxic and harmful gas emissions. In addition, considering environmental protection and economic benefits, the abundance of metal resources such as lithium (Li), nickel (Ni), cobalt (Co), and manganese (Mn) in waste LIBs is very high, exceeding the reserves of natural ores. Therefore, these batteries are considered to be valuable "urban mines" with huge recycling potential.

[0003] Volatile organic compounds (VOCs) are one of the main sources of air pollutants and are also important precursors of secondary organic aerosols (SOAs) and ozone (O3). Therefore, effective control of VOCs emissions is crucial to solving air pollution problems. Among the many VOCs treatment technologies, catalytic oxidation is considered to be one of the most promising technologies because it can completely convert VOCs at lower temperatures, high activity and low cost. For catalytic oxidation, catalysts are the key to large-scale promotion and application. The synthesis of various VOCs oxidation catalysts has become the focus of many researchers.

[0004] Among them, toluene is a highly lipophilic substance that can damage the nervous system. After skin contact, it can cause skin burns or inflammation; long-term contact can cause depression and irregular menstruation. At the same time, the sources of toluene are very wide, mainly from gasoline, transportation and organic solvents. Therefore, toluene degradation has attracted widespread attention. By comparing various toluene oxidation treatment technologies, catalytic oxidation technology has been widely used in pollutant treatment due to its significant advantages such as high removal efficiency, high selectivity and less secondary pollution. In addition, in catalytic oxidation technology, the removal rate of toluene oxidation is highly dependent on the catalyst. Therefore, it is crucial to design and prepare efficient toluene oxidation catalysts. Compared with precious metal catalysts and other transition metal oxides, manganese dioxide has shown good catalytic activity and thermal stability in the removal of volatile organic compounds due to its low price, diverse valence states, abundant resources and environmental friendliness, and has received increasing attention. In addition, studies have shown that the crystal structure and morphology of manganese dioxide catalysts have a great influence on their specific surface area, oxygen vacancy content, lattice oxygen concentration and reducibility, thereby affecting the catalytic performance of VOCs oxidation.

[0005] In this patent, we aim to recycle manganese-based transition metals in waste lithium batteries to develop environmental functional materials, with the goal of using waste pollutants to treat gaseous pollutants. Manganese dioxide catalysts were synthesized using manganese-based transition metals in waste lithium batteries. The performance of the synthesized catalyst was evaluated using typical toluene pollutants as the target pollutant. Summary of the invention

[0006] The purpose of the present invention is to provide a composite crystal manganese-based catalyst, a preparation method and an application thereof. By recycling the positive electrode of waste lithium manganate batteries, a manganese-based catalyst having a 3D structure and a composite of α and δ crystal forms is prepared. The catalyst has a T of 1.13 W / m2 in the catalytic oxidation of toluene. 90 and T 50 All have declined significantly.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is:

[0008] A method for preparing a composite crystalline manganese-based catalyst comprises the following steps:

[0009] S1. preparing positive electrode active powder of waste lithium manganese oxide batteries, and leaching the positive electrode active powder using acid and a reducing agent;

[0010] S2, mixing the leachate with an alkali metal hydroxide and adjusting the pH to 3-6, then adding potassium permanganate and deionized water to obtain a mixed solution; dissolving potassium permanganate and manganese salt in water to obtain a suspension;

[0011] S3, mixing the mixed solution with the suspension and drying; after completion, filtering, washing, drying and calcining in sequence to obtain a composite crystalline manganese-based catalyst.

[0012] Preferably, in step S1, the acid is one or more of nitric acid, sulfuric acid, hydrochloric acid and phosphoric acid;

[0013] The reducing agent is one or more of hydrogen peroxide, sodium bisulfite and glucose;

[0014] The leaching conditions are: 60-80°C, 1-5h, solid-liquid ratio 20:1, and the volume ratio of acid and reducing agent is: (90-110):(4-6).

[0015] Preferably, in step S2, the alkali metal hydroxide is sodium hydroxide and / or potassium hydroxide.

[0016] Preferably, in step S2, when preparing the mixed solution, potassium permanganate and Mn in the leaching solution 2+ The molar ratio is (4.1-6):1.

[0017] Preferably, in step S2, when preparing the suspension, the manganese salt is one or more of manganese nitrate, manganese sulfate and manganese chloride.

[0018] Preferably, in step S2, when preparing the suspension, the manganese salt and the Mn in the leaching solution 2+ The molar ratio is (0.8-1.2):1, and the Mn in potassium permanganate and manganese salt is 2+ The molar ratio is (1-2.5):1.

[0019] Preferably, in step S3, the volume ratio of the mixed solution to the suspension is (0.8-1.2):1.

[0020] Preferably, in step S3, the drying conditions are: 150-170° C., 11-13 h;

[0021] Drying conditions: 50-80℃, 8-24h;

[0022] The calcination conditions are: heating rate 2-6°C / min, target temperature 300-450°C for 1-3h.

[0023] A composite crystalline manganese-based catalyst prepared by any of the above methods, wherein the catalyst has a 3D structure and has both α and δ crystalline MnO2;

[0024] The catalyst contains Mn, Li, Al, Cu and K, and the contents of Mn, Li, Al, Cu and K are 50-60wt%, 0.1-0.3wt%, 0.2-0.4wt%, 0.1-0.3wt% and 3-7wt% respectively.

[0025] Application of the composite crystalline manganese-based catalyst prepared by any of the above methods in catalytic oxidation of toluene.

[0026] The beneficial effects of the present invention are:

[0027] The present invention is based on the recycling of waste lithium batteries and adopts the idea of ​​treating waste with waste to prepare a manganese-based catalyst containing a 3D structure and having both α and δ crystal forms. The number of mesopores in the catalyst is significantly increased, and the specific surface area and pore volume are also greatly improved, making the adsorbed oxygen species more abundant. The combined effect of these factors enables the catalyst to have the best toluene catalytic activity;

[0028] At a toluene concentration of 1000ppm and a mass space velocity of 60000mL·g -1 ·h -1 Under the conditions of T 90 and T 50 At 218℃ and 207℃, the COx yield T 90 and T 50 are 225℃ and 210℃, indicating that the catalyst has excellent catalytic performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 are (a) toluene conversion rate of different catalysts and (b) CO2 yield-reaction temperature curves in the present invention;

[0030] Figure 2 are X-ray diffraction patterns of different catalysts in the present invention;

[0031] Figure 3 are scanning electron microscope images of different catalysts in the present invention;

[0032] Figure 4 is a reduction performance trend diagram of different catalysts in the present invention;

[0033] Figure 5 is the XRD diagram of the catalyst obtained in Comparative Example 4 and Comparative Example 5;

[0034] Figure 6 2 is the XRD diagram of the catalyst obtained in Comparative Example 5 and Comparative Example 6. DETAILED DESCRIPTION

[0035] The present invention will be specifically described below in conjunction with the accompanying drawings and embodiments.

[0036] Example 1

[0037] The catalyst for toluene decomposition provided in this embodiment is a manganese-based catalyst prepared based on waste lithium manganate batteries, and its crystal form is α@δ, named M-α@δ-MnO2, and the catalyst preparation method comprises the following steps:

[0038] (1) The used MLBs cells were fully immersed in a 5% (v%) NaCl solution to discharge them completely.

[0039] (2) Saw open the battery casing, disassemble the battery and classify it into positive electrode material and the remaining parts (negative electrode material, iron shell, separator and electrolyte). The positive electrode material is naturally dried in a fume hood, then cut into small square pieces and calcined at 600°C in a muffle furnace to remove PVDF. The calcined positive electrode pieces are crushed in a pulverizer and sieved to finally obtain the positive electrode active powder.

[0040] (3) Place the above positive electrode active powder in 100 ml of 4 mol·L -1 H2SO4 and 5ml 30% H2O2, the leaching temperature is 70°C, and the leaching time is 2 hours. After the leaching is completed, the mixed solution is filtered through a filter membrane to obtain a clarified leaching solution.

[0041] (4) taking 10 mL of the above leachate and adding sodium hydroxide to adjust the pH of the leachate to 3, then adding 1.697 g of KMnO4 and a certain amount of deionized water to make the solution 50 mL, and stirring to obtain a mixed solution A;

[0042] (5) Dissolve 0.697 g KMnO4 and 0.363 g MnSO4·H2O in 50 mL deionized water and stir to obtain a mixed suspension B;

[0043] (6) Add the mixed solution A to the mixed suspension B, stir for 30 min, put the resulting mixture into a reactor with a polytetrafluoroethylene liner, and place the reactor in a forced air drying oven at 160° C. for 12 h;

[0044] (7) After the reaction is completed, the obtained sample is filtered and then rinsed with deionized water until the filtrate is neutral. The obtained filter residue is placed in a forced air drying oven at 60°C for 24 hours. The dried sample is then placed in a muffle furnace and the heating rate is controlled to be 5°C / min. It is calcined at 350°C for 2 hours. After calcination, it is ground to obtain the M-α@δ-MnO2 catalyst.

[0045] Comparative Example 1

[0046] The catalyst for toluene decomposition provided in this comparative example is a manganese-based catalyst with a crystal form of α@δ, named α@δ-MnO2, and the catalyst preparation method comprises the following steps:

[0047] (1) Dissolve 0.679 g KMnO4 and 0.363 g MnSO4·H2O in 50 mL deionized water and stir continuously for 30 min to obtain a stable suspension.

[0048] (2) 1.697 g KMnO4, 0.363 g MnSO4·H2O and 50 mL deionized water were added to the suspension again and stirred for 30 min.

[0049] (3) The suspension was transferred to a reactor with a polytetrafluoroethylene liner, and the reactor was placed in a forced air drying oven at 160° C. for 12 h;

[0050] (4) After the reaction is completed, the obtained sample is filtered and then rinsed with deionized water until the filtrate is neutral. The obtained filter residue is placed in a forced air drying oven at 60°C for 24 hours. The dried sample is then placed in a muffle furnace, the heating rate is controlled to be 5°C / min, and calcined at 350°C for 2 hours. After calcination, the α@δ-MnO2 catalyst is obtained by grinding.

[0051] Comparative Example 2

[0052] The catalyst for toluene decomposition provided in this comparative example is a manganese-based catalyst with an α crystal form, named α-MnO2, and the catalyst preparation method comprises the following steps:

[0053] (1) Dissolve 1.358 g KMnO4 and 0.726 g MnSO4·H2O in 100 mL ultrapure water and stir continuously for 30 min to obtain a stable suspension.

[0054] (2) transferring the suspension into a reactor with a polytetrafluoroethylene liner, and placing the reactor in a forced air drying oven at 160° C. for 12 h;

[0055] (3) After the reaction is completed, the obtained sample is filtered and then rinsed with deionized water until the filtrate is neutral. The obtained filter residue is placed in a forced air drying oven at 60°C for 24 hours. The dried sample is then placed in a muffle furnace, the heating rate is controlled to be 5°C / min, and calcined at 350°C for 2 hours. After calcination, it is ground to obtain an α-MnO2 catalyst.

[0056] Comparative Example 3

[0057] The catalyst for toluene decomposition provided in this comparative example is a manganese-based catalyst with a δ crystal form, named δ-MnO2, and the catalyst preparation method comprises the following steps:

[0058] (1) Dissolve 3.394 g KMnO4 and 0.726 g MnSO4·H2O in 100 mL deionized water and stir continuously for 30 min to obtain a stable suspension.

[0059] (2) transferring the suspension into a reactor with a polytetrafluoroethylene liner, and placing the reactor in a forced air drying oven at 160° C. for 12 h;

[0060] (3) After the reaction is completed, the obtained sample is filtered and then rinsed with deionized water until the filtrate is neutral. The obtained filter residue is placed in a forced air drying oven at 60°C for 24 hours. The dried sample is then placed in a muffle furnace, the heating rate is controlled to be 5°C / min, and calcined at 350°C for 2 hours. After calcination, the δ-MnO2 catalyst is obtained by grinding.

[0061] Comparative Example 4

[0062] This comparative example provides a manganese-based catalyst with a pH value of 1 adjusted to the leachate, named M-MnO2-pH 1. The catalyst preparation method is substantially the same as that of Example 1, except that the following steps are performed:

[0063] (1) 10 mL of the leachate was added with sodium hydroxide to adjust the pH of the leachate to 1, and then 1.697 g of KMnO4 and a certain amount of deionized water were added to make the solution 50 mL, and the mixture was stirred to obtain a mixed solution A;

[0064] (2) transferring the suspension into a reactor with a polytetrafluoroethylene liner, and placing the reactor in a forced air drying oven at 160° C. for 12 h;

[0065] (3) After the reaction is completed, the obtained sample is filtered and then rinsed with deionized water until the filtrate is neutral. The obtained filter residue is placed in a forced air drying oven at 60°C for 24 hours. The dried sample is then placed in a muffle furnace and the heating rate is controlled to be 5°C / min. It is calcined at 350°C for 2 hours. After calcination, it is ground to obtain the M-MnO2-pH 1 catalyst.

[0066] Comparative Example 5

[0067] This comparative example provides a manganese-based catalyst with a pH value of the leachate adjusted to 3, named M-MnO2-pH 3. The catalyst preparation method is basically the same as that of Example 1, except that the following steps are performed:

[0068] (1) 10 mL of the leachate was added with sodium hydroxide to adjust the pH of the leachate to 3, and then 1.697 g of KMnO4 and a certain amount of deionized water were added to make the solution 50 mL, and the mixture was stirred to obtain a mixed solution A;

[0069] (2) transferring the suspension into a reactor with a polytetrafluoroethylene liner, and placing the reactor in a forced air drying oven at 160° C. for 12 h;

[0070] (3) After the reaction, the obtained sample was filtered and rinsed with deionized water until the filtrate was neutral. The obtained filter residue was placed in a forced air drying oven at 60°C for 24 h. The dried sample was then placed in a muffle furnace and the heating rate was controlled to be 5°C / min. It was calcined at 350°C for 2 h. After calcination, it was ground to obtain the M-MnO2-pH 3 catalyst, which was further named M-MnO2-5.

[0071] The XRD patterns of the samples of Comparative Example 4 and Comparative Example 5 are as follows: Figure 5 As shown in the figure, it can be seen that the δ-crystalline MnO2 is not generated in the M-MnO2-pH 1 catalyst, indicating that if the pH value of the leaching solution is not adjusted to 3 or above, the catalyst crystal form cannot be changed to the δ-crystalline form. Therefore, if the pH value of the leaching solution cannot be adjusted to 3 or above in step (4) of Example 1, the α@δ composite crystalline MnO2 cannot be generated.

[0072] Comparative Example 6

[0073] This comparative example provides a manganese-based catalyst in which the pH value of the leachate is adjusted to 3 and the ratio of potassium permanganate to manganese ions in the leachate is 2:1, named M-α-MnO2-2. The catalyst preparation method is basically the same as that in Example 1, except that the following steps are performed:

[0074] (1) 10 mL of the leachate was added with sodium hydroxide to adjust the pH of the leachate to 3, and then 0.697 g of KMnO4 and a certain amount of deionized water were added to make the solution 50 mL, and the mixture was stirred to obtain a mixed solution A;

[0075] (2) transferring the suspension into a reactor with a polytetrafluoroethylene liner, and placing the reactor in a forced air drying oven at 160° C. for 12 h;

[0076] (3) After the reaction is completed, the obtained sample is filtered and then rinsed with deionized water until the filtrate is neutral. The obtained filter residue is placed in a forced air drying oven at 60°C for 24 hours. The dried sample is then placed in a muffle furnace, the heating rate is controlled to be 5°C / min, and calcined at 350°C for 2 hours. After calcination, the M-MnO2-2 catalyst is obtained by grinding.

[0077] The XRD patterns of the samples of Comparative Example 5 and Comparative Example 6 are as follows: Figure 6 As shown in the figure, it can be seen that the M-MnO2-2 catalyst does not generate δ-crystalline MnO2, indicating that if the ratio of potassium permanganate to manganese ions in the leaching solution is less than 5:1, the resulting catalyst crystal cannot be converted into δ-crystalline. Therefore, if sufficient KMnO4 is not added in step (4) of Example 1, α@δ composite crystal MnO2 cannot be generated.

[0078] Characterization Test

[0079] The XRD patterns of α-MnO2, δ-MnO2, α@δ-MnO2, and M-α@δ-MnO2 were compared and studied. Figure 2 As shown. The characteristic peaks of α-MnO2 and δ-MnO2 can be observed simultaneously in the spectra of α@δ-MnO2 and M-α@δ-MnO2, indicating that both α and δ crystal forms exist in the two samples. In addition, the diffraction peak of M-α@δ-MnO2 is weaker and broader than that of α@δ-MnO2, indicating that waste LIBs have lower crystallinity than α@δ-MnO2 prepared from pure substances. The average grain size of α-MnO2, δ-MnO2, α@δ-MnO2, and M-α@δ-MnO2 was further estimated by the Scherrer formula (see Table 1). The average grain size of M-α@δ-MnO2 is the smallest, which is 5.9nm, verifying the above conclusion. For the same transition metal oxide, the smaller the grain size, the higher the free energy of its surface, which is more conducive to the adsorption and activation of VOCs molecules on its surface during catalytic oxidation.

[0080] Table 1 Crystal size and structural parameters of each catalyst

[0081]

[0082] Figure 3 (A1-D2 area) is the SEM spectrum of each sample. α-MnO2 is composed of randomly stacked nanorods with smooth surfaces. The diameter and length of a single nanorod are approximately 50-100nm and 1-5μm, respectively. δ-MnO2 has a tremella-like spherical structure with an average diameter of about 500nm. Each spherical structure is connected by many uniform and curved ultrathin nanosheets. Nanorods and nanospheres or blocks (interconnected nanosheets) can be found in the SEM spectra of α@δ-MnO2 and M-α@δ-MnO2, indicating that it is coupled by α-MnO2 and δ-MnO2. The single structural unit of M-α@δ-MnO2 is smaller and more messy, proving that it has a smaller grain size. The TEM spectra of each sample are shown in Figure 3 (A3-D3 area), rod-like and lamellar structures can be observed in both α@δ-MnO2 and M-α@δ-MnO2, verifying the inference of SEM.

[0083] The lattice characteristics of each sample were further observed using HRTEM, such as Figure 3 (A4-D4 area). Figure 3 The lattice fringes in (A4 region) are clear and uniform, and the spacing between the two fringes is 0.49 nm, which is consistent with the crystal plane spacing of the (200) plane of α-MnO2. Figure 3The lattice spacing of 0.69nm and 0.79nm in (B4 area) indicates that the main exposed crystal plane is the (011) crystal plane of δ-MnO2. The lattice spacing of α@δ-MnO2 and M-α@δ-MnO2 are 0.49nm and 0.70nm, respectively, belonging to the (200) plane of α-MnO2 and the (011) plane of δ-MnO2. The HRTEM spectrum once again confirms the inference drawn from XRD, SEM and TEM, that is, α-MnO2 and δ-MnO2 coexist in α@δ-MnO2 and M-α@δ-MnO2.

[0084] Among the prepared catalysts, M-α@δ-MnO2 has the smallest average grain size of 5.9 nm, indicating that its surface has a higher free energy, which is more conducive to the adsorption and activation of VOCs molecules during catalytic oxidation. Compared with other samples, M-α@δ-MnO2 has the largest specific surface area and the largest pore volume, which are 118 m 2 ·g -1 and 0.472cm 3 ·g -1 , with abundant gas-solid interface and excellent diffusion capacity, is conducive to the efficient degradation of toluene oxidation.

[0085] At the same time, the present invention further studies the reduction performance of each catalyst using H2-TPR experiments, such as Figure 4 As shown. All samples have an asymmetric broad peak in the temperature range of 100-500℃, and its shape is different, indicating that there are certain differences in the reduction characteristics of the four MnO2. The reduction peak of each sample can be decomposed into four sub-peaks, which are named I, II, III and IV according to the position of the peak from low temperature to high temperature. Sub-peak I is related to the reduction of surface adsorbed oxygen species, while peaks II, III and IV can be attributed to the gradual reduction of MnO2→Mn2O3→Mn3O4→MnO, respectively. By comparison, the reduction peaks of α@δ-MnO2 are lower than those of α-MnO2 and δ-MnO2, and the reduction peaks of M-α@δ-MnO2 are lower than those of α-MnO2, indicating that 3D structured α@δ-MnO2 and M-α@δ-MnO2 can be reduced at lower temperatures than the corresponding 1D and 2D structured α-MnO2 and δ-MnO2. This also means that the oxygen species of 3D structured MnO2 have relatively high mobility, which is conducive to promoting the redox process and making the catalyst more active. Similarly, the manganese-based catalyst prepared from waste LIBs has better catalytic performance than the manganese-based catalyst prepared from pure substances. The total hydrogen consumption of five MnO2 was calibrated with standard CuO The order from small to large is: α-MnO2 (12.9mmol·g -1 )>δ-MnO2(8.3mmol·g -1)>α@δ-MnO2(7.4mmol·g -1 )>M-δ-MnO2(7.2mmol·g -1 )>M-α@δ-MnO2(6.5mmol·g -1 ). Catalyst The larger the value, the more oxygen species are involved in the reduction reaction, that is, the fewer oxygen vacancies. According to the above results, the 3D structure of α@δ composite crystal MnO2 has more bulk oxygen vacancies than the corresponding 1D and 2D structure of α and δ single crystal MnO2. In addition, M-α@δ-MnO2 prepared from waste LIBs has the most bulk oxygen vacancies.

[0086] It can be seen from the results of ICP-OES (Table 3) that compared with α@δ-MnO2, M-α@δ-MnO2 contains a small amount of Li, Al, and Cu doping. It can be inferred that the three doped metal elements in M-α@δ-MnO2 have the effect of enhancing the physical and chemical properties of the catalyst.

[0087] Table 2 ICP-OES results of leachate and catalysts

[0088]

[0089]

[0090] In Table 2, the unit of Ⅰ is mg·L -1 ; ⅡThe unit is mass percentage (wt%).

[0091] Activity test

[0092] The catalytic performance of toluene oxidation was studied in a fixed bed experimental device. The reactor is a quartz tube with an inner diameter of 6 mm. The reaction temperature is controlled by a program temperature control device, and the temperature is measured using a self-prepared thermocouple. In the experiment, the initial concentration of toluene was set to about 1000 ppm, and high-purity liquid toluene was placed in an ice water bath. Toluene gas was formed by bubbling, and the toluene gas was mixed with another air and diluted in a buffer bottle. The catalyst dosage was 0.06 g, and the particle size was 40-60 mesh, which was obtained by screening. The gas flow rate of each channel was controlled by a mass flow meter, and the total gas flow rate was controlled at 60 mL min -1 The reaction gas hourly space velocity was set to 60000 mL·g -1 ·h -1 .

[0093] The test results are as follows Figure 1As shown in Table 3, in the reaction temperature range of 150-300℃, the toluene conversion rate and CO2 yield of 3D structured α@δ-MnO2 and M-α@δ-MnO2 are higher than those of 1D tunnel structured α-MnO2 and 2D layered structured δ-MnO2. 90 and T 50 At 240℃ and 231℃, the COx yield T 90 and T 50 The conversion rate of toluene catalytic oxidation of M-α@δ-MnO2 is 255℃ and 237℃. 90 and T 50 At 218℃ and 207℃, the COx yield T 90 and T 50 is 225℃ and 210℃, indicating that the M-α@δ-MnO2 catalyst has better catalytic activity at both high and low temperatures. 90 =218℃, T 50 =207℃)<α@δ-MnO2(T 90 =240℃, T 50 =231℃)<α-MnO2(T 90 =258℃, T 50 =246℃)<δ-MnO2(T 90 =285℃, T 50 =244°C). The order of COx yields of the catalysts is consistent with the above order.

[0094] Table 3 Reaction conditions and catalytic performance of each catalyst

[0095]

[0096] The reason is that compared with the single crystal α-MnO2 and δ-MnO2 with 1D and 2D structures, the α@δ-MnO2 with 3D structure has more mesopores, larger specific surface area and pore volume, and thus has better catalytic activity for toluene. The three doped metal elements in M-α@δ-MnO2 have the effect of strengthening the physical and chemical properties of the catalyst, significantly increasing the number of mesopores in the 3D structure M-α@δ-MnO2, and greatly improving the specific surface area and pore volume. Therefore, M-α@δ-MnO2 exhibits better toluene catalytic activity than α-MnO2, δ-MnO2, and α@δ-MnO2.

[0097] In summary, the manganese-based catalyst prepared by recycling waste lithium batteries in the present invention has a 3D structure and a composite of α and δ crystal forms, with significantly increased number of mesopores, greatly improved specific surface area and pore volume, and excellent toluene catalytic activity. -1 ·h -1 Under the conditions of catalytic oxidation toluene conversion rate T 90 and T 50 At 218℃ and 207℃, the COx yield T 90 and T 50 are 225℃ and 210℃, indicating that the catalyst has excellent catalytic performance.

[0098] The above is only a preferred implementation of the patent of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the patent of the present invention. These improvements and modifications should also be regarded as the scope of protection of the patent of the present invention.

Claims

1. A method for preparing a composite crystalline manganese-based catalyst, characterized in that: The steps include: S1. preparing positive electrode active powder of waste lithium manganese oxide batteries, and leaching the positive electrode active powder using acid and a reducing agent; S2, mixing the leachate with an alkali metal hydroxide and adjusting the pH to 3-6, then adding potassium permanganate and deionized water to obtain a mixed solution; dissolving potassium permanganate and manganese salt in water to obtain a suspension; S3, mixing the mixed solution with the suspension and drying; after completion, filtering, washing, drying and calcining in sequence to obtain a composite crystalline manganese-based catalyst.

2. The method for preparing the composite crystalline manganese-based catalyst according to claim 1, characterized in that: In step S1, the acid is one or more of nitric acid, sulfuric acid, hydrochloric acid and phosphoric acid; The reducing agent is one or more of hydrogen peroxide, sodium bisulfite and glucose; The leaching conditions are: 60-80°C, 1-5h, solid-liquid ratio 20:1, and the volume ratio of acid and reducing agent is: (90-110):(4-6).

3. The method for preparing the composite crystalline manganese-based catalyst according to claim 1, characterized in that: In step S2, the alkali metal hydroxide is sodium hydroxide and / or potassium hydroxide.

4. The method for preparing the composite crystalline manganese-based catalyst according to claim 1, characterized in that: In step S2, when preparing the mixed solution, potassium permanganate and Mn in the leaching solution 2+ The molar ratio is (4.1-6):

1.

5. The method for preparing the composite crystalline manganese-based catalyst according to claim 1, characterized in that: In step S2, when preparing the suspension, the manganese salt is one or more of manganese nitrate, manganese sulfate and manganese chloride.

6. The method for preparing the composite crystalline manganese-based catalyst according to claim 1, characterized in that: In step S2, when preparing the suspension, the manganese salt and the Mn in the leaching solution 2+ The molar ratio is (0.8-1.2):1, and the Mn in potassium permanganate and manganese salt is 2+ The molar ratio is (1-2.5):

1.

7. The method for preparing the composite crystalline manganese-based catalyst according to claim 1, characterized in that: In step S3, the volume ratio of the mixed solution to the suspension is (0.8-1.2):

1.

8. The method for preparing the composite crystalline manganese-based catalyst according to claim 1, characterized in that: In step S3, the drying conditions are: 150-170°C, 11-13h; Drying conditions: 50-80℃, 8-24h; The calcination conditions are: heating rate 2-6°C / min, target temperature 300-450°C for 1-3h.

9. A composite crystalline manganese-based catalyst prepared by the method according to any one of claims 1 to 8, characterized in that: The catalyst is a 3D structure and has both α and δ crystal forms of MnO2; The catalyst contains Mn, Li, Al, Cu and K, and the contents of Mn, Li, Al, Cu and K are 50-60wt%, 0.1-0.3wt%, 0.2-0.4wt%, 0.1-0.3wt% and 3-7wt% respectively.

10. Use of the composite crystalline manganese-based catalyst prepared by the method according to any one of claims 1 to 8 in catalytic oxidation of toluene.